The Effect of Post-Cardiopulmonary Resuscitation N-acetylcysteine on Renal Function: A Randomized Clinical Trial - Gita Shoeibi; Atabak Najafi; Mostafa Sadeghi; Shaqayeq Marashi; Golnaz Moghimi; Mehdi Sanatkar; Amir Abbas Yaghooti (Archives of Anesthesia and Critical Care, 2016)
Background: The purpose of our study was to determine the effect of N-acetylcysteine (NAC) administered after successful cardiopulmonary resuscitation (CPR) on renal function of the survived patients. Methods: In this double-blinded randomized clinical trial, 44 patients who experienced cardiopulmonary arrest and underwent successful cardiopulmonary resuscitation (CPR) were entered into the study. They were randomly divided into two groups. One group received NAC (150 mg/kg) and the control group received normal saline (NS). Results: Serum levels of blood urea nitrogen (BUN), creatinine, and neutrophil gelatinase-associated lipocalin (NGAL) were significantly lower in the NAC group when compared to the NS group at 6, 12,24, 48, and 72 hours after resuscitation. However, alanine aminotransferase (ALT), cardiac troponin, creatine kinase MB fraction (CK-MB) and arterial blood gases did not differ between the two groups. Conclusion: We observed significantly lower serum levels of BUN, creatinine, and NGAL in patients who received NAC after successful CPR following cardiopulmonary arrest. This can be used in clinical practice to decrease the chance of developing renal failure in such patient population.